ANALISIS PENGAMBILAN KEPUTUSAN DALAM MEMECAHKAN MASALAH MATEMATIS DITINJAU DARI GAYA KOGNITIF SISWA KELAS VII SMP NEGERI 24 PONTIANAK - Aulianata, Yuli; Muchtadi; Sandie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe how decisions are made in solving mathematical problems in terms of field dependent and field independent cognitive styles. This type of research is qualitative research with a descriptive method in the form of a case study. The research subjects were 2 students from class VII C of SMP Negeri 24 Pontianak, namely 1 field dependent subject and 1 field independent subject taken based on considerations and suggestions from the subject teacher. The data collection techniques used were the Group Embedded Figures Test (GEFT) instrument test, essay test questions for decision making in solving mathematical problems, as well as non-tests in the form of interviews and documentation. To test the validity of the data, triangulation techniques were used. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Test and interview results are analyzed based on decision making indicators, namely: understanding the problem in the questions given, identifying the purpose of decision making, finding alternative answers, calculating or working on the questions given, evaluating alternative answers to be worked on, making decisions, evaluating decision results. These results indicate that students with a field dependent cognitive style can fulfill all decision making indicators in solving decision making test questions. Students with field independent cognitive style are only able to fulfill some of all decision making indicators.